Cost‐effectiveness analysis of postoperative surveillance for stage IV colorectal cancer in Japan: An economic modeling study - Fumio Tsukamoto; Shunsuke Tsukamoto; Takeharu Kato; Hiroshi Nagata; Yasuyuki Takamizawa; Konosuke Moritani; Yusuke Kinugasa; Minoru Esaki; Yukihide Kanemitsu; Ataru Igarashi (Annals of Gastroenterological Surgery)
Abstract Background The optimal postoperative surveillance strategy after curative resection in patients with stage IV colorectal cancer remains unclear. The present study aimed to assess the cost‐effectiveness of postoperative surveillance strategies recommended by the various academic societies for stage IV colorectal cancer after curative resection. Methods This economic evaluation used a Markov state‐transition model to compare the cost‐effectiveness of postoperative surveillance programs proposed in guidelines published by the American Society of Clinical Oncology, American Society of Colon and Rectal Surgeons, European Society for Medical Oncology, National Comprehensive Cancer Network, and Japanese Society for Cancer of the Colon and Rectum. Model parameters were extracted from our retrospective data for patients with colorectal cancer who had synchronous liver and/or lung metastases and underwent curative resection. Cost‐effectiveness was assessed using an incremental cost‐effectiveness ratio for quality‐adjusted life years, with a maximum acceptable value of 5 000 000–6 000 000 JPY/33333–40 000 USD. Uncertainty in the model was assessed by probabilistic sensitivity analyses. Results For patients with stage IV colorectal cancer after curative resection, the JSCCR‐strategy was the most cost‐effective, with an incremental cost‐effectiveness ratio of 2 888 628 JPY/19256 USD compared with the next most cost‐effective program. Probabilistic sensitivity analysis showed that the JSCCR‐strategy was most likely to be selected as the most cost‐effective (76.1%–77.9%). Conclusions This modeling analysis found that the JSCCR‐strategy was the most cost‐effective strategy for stage IV colorectal cancer. Our findings suggest that intensive postoperative surveillance is acceptable for stage IV colorectal cancer.